Time interval from ovulation to extrusion in female bullfrog in different photoperiods - Agostinho, Claudio Angelo [UNESP]; Wechsler, Francisco Stefano [UNESP]; Castro, Cecilia Silva de [UNESP]; Agostinho, Lucas Miyabara [UNESP]; Ribeiro, Raphaela Rezende [UNESP]; Agostinho, Sueli Matiko Miyabara (Sociedade Brasileira de Zootecnia, 2011)
It was analyzed in this work the influence of photoperiod on time interval from ovulation induction period to extrusion of ovocits in female bullfrogs (Lithobates catesbeianus). It was used 54 females reared from metamorphosis to 9 months of age under three photoperiods: dark time (DL 0:24), 16 hours of daylight (DL 16:8) and 12 hours of daylight (DL 12:12). Ovulation was induced by intramuscular application of two doses of LHRHa with 12 hours of interval between the injections. After 10, 25, 28, 31, 34 and 37 hours from the first hormone injection, 10-gram samples (3,000 eggs) were extracted from each female at each time interval and fertilized. Egg hatching rate was checked in each sample 72 hours after fertilization. Analysis of variance showed a significant effect of extrusion delay and the interaction between photoperiod and this delay. Extrusion should be carried out 33, 24 and 26 hours after the first hormone dosage in females reared in environments without light, with 12 hours of daylight and with 16 hours of daylight, respectively, to obtain the maximum fertilization rate.
Keywords: artificial fertilization; controlled reproduction; fertilization rate; frog reproduction; Lithobathes catesbeianus; spawning